THE ROLE AND IMPORTANCE OF DEVELOPING LEARNING EXPERIENCES IN INCREASING LEARNING EFFECTIVENESS - Bakhtiar, Yusup Hamdani; Dedih, Ujang; Nugraha, Mulyawan Safwandy (INTIHA: Islamic Education Journal, 2024)
The aim of this research is to obtain information about the effectiveness of learning in the Roudhotul Muta'allimin Kindergarten class, Kadipaten District, Tasikmalaya Regency. This research method uses qualitative research with a case study type of research using the Milles and Huberman model of data analysis. Based on the research findings, it shows that: (1) Learning is effective because there is habituation and there is conformity between the school's vision and mission in realizing quality education, (2) There is teacher readiness in planning learning as well as the teacher's attitude and ability in providing an example to children, (3) the success of parents in achieving effective learning for children cannot be separated from the parenting style of parents which is influenced by the socio-economic background of the family and the intensity of time spent with children, (4) Community concern in helping schools succeed in providing effective learning, (5) The form of cooperation between stakeholders is carried out by establishing communication and involvement in school activities.